The influence of corporate governance on commercial bank financial performance with the mediating role of disclosure of financial instruments - Nguyen Thi Thu , Hien (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The paper examines the impact of corporate governance on the financial performance of banks with the mediating role of financial instrument disclosure (FID). The study utilizes a sample of 21 banks in Vietnam and employs multiple regression analysis with panel data spanning 14 years, from 2010 to 2023. Sobel-Goodman and Bootstrap tests are used to assess the mediating role of FID. The results show that the level of conformity with the requirements of International Financial Reporting Standard (IFRS 7) is about 36.8%. The study provides evidence of the mediating role of FID in the relationship between executive members, foreign ownership, and financial performance. In addition, educational attainment, executive participation, and foreign ownership contribute to increasing the financial performance of banks, which is explained by the agency theory and the resource dependence theory. The research implications suggest that Vietnam should establish accounting standards for FID as soon as possible. Banks, in turn, need to implement appropriate accounting policies for FID to further contribute to improving financial performance.